Uma análise das relações comprador-fornecedor na cadeia de suprimentos de produtos orgânicos no Brasil - Silva, Silvio Bitencourt da (Universidade do Vale do Rio dos Sinos, 2010)
This paper presents an analysis of buyer-supplier relationships in the supply chain for organic products in Brazil through a case study on how to characterize the relationships between the Pão de Açúcar and their suppliers of fruit and vegetables ( FLV) involved in the supply chain to its own brand Taeq Taeq Organic product line. The theoretical framework combines concepts of retail, operations strategy, value chain and network operations, supply chain management and buyer-supplier relationships. The buyer-supplier relationships are presented in accordance with benchmark analysis discussed from two perspectives episodes of interaction and relationships that together define the operating environment in which buyers and suppliers interact, including the reduction in the supplier base, the long-term relationship the supplier involvement in product development and quality as a priority criterion for selecting and evaluating suppliers, as well as the dimensions of the relationships created in this context that include communication, cross-functional teams, commitment, cooperation, and joint operations. Differences are observed in the characterization of relationships from the retail on all observed characteristics in relation to established between intermediate wholesaler, producer-engineer and producer. It is perceived that relationships between buyers and suppliers in the supply chain for organic products from a large retail chain is characterized by an asymmetry reflected in the ability of retailers to exercise power, influence or control over the supply chain due to its purchasing power and proximity to the final consumer, and the search for efficiency, depending on the need for retail to improve the cost / benefit analysis of its processes which, at times, impacting on confidence between the parties, besides the dependence of retail against suppliers depending on availability of products that meet current demand. However, the practical relationship between the buyer and its suppliers are constantly changing due to major changes in the environments and the increasing need to respond more quickly to customer needs, which implies a dynamic that allows the identification of structures diverse and unique. Additionally, one realizes that the quest for differentiation of the retailer through the introduction of a social dimension in its value proposition, in association with their own brands of organic products does not ensure the extension to the entire supply chain for organic products, the benefits to society to encourage the inclusion of small producers into supply chains more elaborate, promote improved health of farmers to adopt organic farming without using pesticides.
Keywords: Relações comprador-fornecedor; Cadeia de suprimentos; Orgânicos; Produtores rurais; Varejo; Buyer-supplier relations; Supply chain; Organic farmers; Retailers; ACCNPQ::Ciências Sociais Aplicadas::Administração